Mechanism of steam chamber expansion and economic and technical limits of injection and production in VHSD development for extra-heavy oil reservoirs - SHAO Guolin (Youqi dizhi yu caishoulu)
Extra-heavy oil reservoirs generally have high oil viscosity and poor mobility， resulting in unsatisfactory performance of the conventional cyclic steam stimulation （CSS） development. Compared to CSS， vertical-horizontal well steam drive （VHSD） development can increase the recovery by more than 10%. An extra-heavy oil block in the eastern Shengli Oilfield was taken as an example， and a laboratory-scale model established based on similarity principles was combined with numerical methods to investigate the VHSD development mechanism， thereby determining the steam chamber expansion process and key factors influencing development. The research results indicate that ① the steam chamber first expands independently and then connects in a “concave” shape during the VHSD process. The steam chamber increases with the increase in steam injection volume after the thermal connection is realized. The oil production decreases， and the final recovery of the experiment is 55.42% when the steam chamber expands to the horizontal well. ② In the preheating stage of huff and puff， the amount of steam injected in a single cycle is not more than 1 600 m3， and the oil production time is not more than 150 d； the well shut-in lasts for 5-10 d， and the effective preheating of the reservoir can be realized after 3-4 cycles. ③ The steam injection rate in the VHSD stage does not exceed 60 m3/d， and the production-injection ratio does not exceed 1.1. Among the influencing factors， the steam injection rate and steam dryness of VHSD have the greatest influence on the expansion and development of the steam chamber.